Regeneration of the cerebral cortex by direct chemical reprogramming of macrophages into neuronal cells in acute ischemic stroke - Ninomiya, Itaru; Koyama, Akihide; Otsu, Yutaka; Onodera, Osamu; Kanazawa, Masato (Frontiers in Cellular Neuroscience, 2023)
Theoretically, direct chemical reprogramming of somatic cells into neurons in the infarct area represents a promising regenerative therapy for ischemic stroke. Previous studies have reported that human fibroblasts and astrocytes transdifferentiate into neuronal cells in the presence of small molecules without introducing ectopic transgenes. However, the optimal combination of small molecules for the transdifferentiation of macrophages into neurons has not yet been determined. The authors hypothesized that a combination of small molecules could induce the transdifferentiation of monocyte-derived macrophages into neurons and that the administration of this combination may be a regenerative therapy for ischemic stroke because monocytes and macrophages are directly involved in the ischemic area. Transcriptomes and morphologies of the cells were compared before and after stimulation using RNA sequencing and immunofluorescence staining. Microscopic analyses were also performed to identify cell markers and evaluate functional recovery by blinded examination following the administration of small molecules after ischemic stroke in CB-17 mice. In this study, an essential combination of six small molecules (CHIR99021, Dorsomorphin, Forskolin, isoxazole-9 [ISX-9], Y27632, and DB2313) that transdifferentiated monocyte-derived macrophages into neurons in vitro was identified. Moreover, administration of six small molecules after cerebral ischemia in model animals generated a new neuronal layer in the infarct cortex by converting macrophages into neuronal cells, ultimately improving neurological function. These results suggest that altering the transdifferentiation of monocyte-derived macrophages by the small molecules to adjust their adaptive response will facilitate the development of regenerative therapies for ischemic stroke.